The Prevalence of anemia among informal primary school children: a community based study in Rural Upper Egypt - Rasha Aziz Salama; Meray R Labib (Epidemiology, Biostatistics and Public Health)
Abstract: Background: Anemia has been recognized as a major public health problem in developing countries. The magnitude of anemia among school children has received less attention compared with that in preschoolers and pregnant women. This study aimed to estimate the prevalence of anemia and to assess its associated factors among informal school children in rural Upper Egypt. Methods: A cross sectional descriptive study was conducted in a randomly selected Girls Education initiative schools in three Egyptian governorates for duration of 11 months. A structured questionnaire was used to collect sociodemographic data from 2826 children aged 6-19 years. Hemoglobin concentration and anthropometric indicators were assessed using the World Health Organization guidelines. Stool samples were examined for parasitic infestations, using the Kato Katz technique. The objective of the study was adequately explained to participants’ guardian and their consensus was obtained with assured confidentiality. Results: the prevalence of anemia among these children was 59.3%, out of which, 82.5% had mild anemia and 17.4% of them had moderate anemia. It was significantly higher among 64% of children in age group 6-9years and 61.3% of females. The majority of underweight children (75.8%) and 66.4% of children with parasitic infestation were anemic. Conclusions: Anemia remains a common problem among GEI School particularly the young children and girls of low income household. School children should be screened periodically and appropriate measures should be taken in order to promote health and guide effective education sector reform initiatives.   Keywords: Anemia, GEI schools, Rural Upper Egypt